IL-1RAcPb signaling regulates adaptive mechanisms in neurons that promote their long-term survival following excitotoxic insults - Gosselin, David; Bellavance, Marc-Andre; Rivest, Serge (Frontiers in Cellular Neuroscience, 2013)
Excitotoxicity is a major component of neurodegenerative diseases and is typically accompanied by an inflammatory response. Cytokines IL-1alpha and IL-1beta are key regulators of this inflammatory response and modulate the activity of numerous cell types, including neurons. IL-1RAcPb is an isoform of IL-1RAcP expressed specifically in neurons and promotes their survival during acute inflammation. Here, we investigated in vivo whether IL-1RAcPb also promotes neuronal survival in a model of excitotoxicity. Intrastriatal injection of kainic acid in mice caused a strong induction of IL-1 cytokines mRNA in the brain. The stress response of cortical neurons at 12 hours post-injection, as measured by expression of Atf3, FoxO3a and Bdnf mRNAs, was similar in WT and AcPb-deficient mice. Importantly however, a delayed upregulation in the transcription calpastatin was significantly higher in WT than in AcPb-deficient mice. Finally, although absence of AcPb signaling had no effects on neuronal damage in the cortex at early time points, it significantly impaired their long-term survival. These data suggest that in a context of excitotoxicity, stimulation of IL-1RAcPb signaling may promote the activity of a key neuroprotective mechanism.